2019
DOI: 10.1021/acs.jpcb.9b04541
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Elusive Hydration of Pb2+from the Gas Phase to the Liquid Aqueous Solution: Modeling the Hemidirected Solvation with a Polarizable MCDHO Force-Field

Abstract: The Pb2+ presents unique hydration features that make the experimental characterization and its theoretical modeling challenging: classical molecular dynamics (MD) with standard force-fields fails to produce the experimentally determined diffusion coefficient and the EXAFS spectrum. Here we study the hydration of Pb2+ in aqueous solution employing a polarizable model compatible with the MCDHO water model. The MCDHO FF for the Pb2+–water interaction was fitted to reproduce the configurations and interaction ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…All obtained structures of Pb-water clusters were characterized by a minimum Pb-O distance in the 2.27-2.43 Å range (Table 1), although, by increasing the number of water molecules (n > 4), we also detected slightly longer Pb-O distance, typically in the 2.47-2.87 Å range (Table 1), consistently with available computational data [55,56]. The calculated values of O-Pb-O angles for the n < 7 species were mostly detected in the range of either 64-75 (proximal) or 132-135 (distal) degrees, in agreement with octahedral-like spatial orientations of the ligands bound at the metal center as also reported by others [55][56][57][58][59][60][61][62]. Interestingly, all water molecules were detected in the first coordination sphere of both n = 7 and n = 9 species, whereas the Pb(II) center of the n = 8 complex was found to be coordinated by only six water molecules (Table 1).…”
Section: The Pb(ii) Coordination In Pure Water or Thiol/ Thiolate Aqueous Systemssupporting
confidence: 89%
See 1 more Smart Citation
“…All obtained structures of Pb-water clusters were characterized by a minimum Pb-O distance in the 2.27-2.43 Å range (Table 1), although, by increasing the number of water molecules (n > 4), we also detected slightly longer Pb-O distance, typically in the 2.47-2.87 Å range (Table 1), consistently with available computational data [55,56]. The calculated values of O-Pb-O angles for the n < 7 species were mostly detected in the range of either 64-75 (proximal) or 132-135 (distal) degrees, in agreement with octahedral-like spatial orientations of the ligands bound at the metal center as also reported by others [55][56][57][58][59][60][61][62]. Interestingly, all water molecules were detected in the first coordination sphere of both n = 7 and n = 9 species, whereas the Pb(II) center of the n = 8 complex was found to be coordinated by only six water molecules (Table 1).…”
Section: The Pb(ii) Coordination In Pure Water or Thiol/ Thiolate Aqueous Systemssupporting
confidence: 89%
“…Preliminary DFT calculations were carried out to investigate in detail the composition and the structure of both Pb(II)-water and Pb(II)-thiol/thiolate binary systems, the latter being small model of the lead coordination occurring in proteins. The investigation of the Pb(II) hydration at high level of theory reported by others [55,56,[58][59][60][61] predicted the holo-directed coordination of up to nine water molecules. In our DFT study, the incremental coordination of water molecules to the Pb(II) showed that, although optimized structures with up to nine H 2 O in the first coordination sphere could be obtained, the most stable [Pb(H 2 O) n ] 2+ complexes were characterized by n = 4 or 6 and, again, holo-directed coordination geometry (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of EXAFS , and DFT Pb–O distances, we assume that [Pb­(H 2 O) 6 ] 2+ is more abundant than [Pb­(H 2 O) 4 ] 2+ in aqueous solution, although the relative energies suggest otherwise. Given that previous theoretical studies have obtained varying results depending on the level of theory, only DFT-based molecular dynamics simulations in explicit solvent using the same level of theory could clarify the actual situation, but such an investigation is beyond the scope of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Given that previous theoretical studies have obtained varying results depending on the level of theory,103 only DFT-based molecular dynamics simulations in explicit solvent using the same level of theory could clarify the actual situation, but such an investigation is beyond the scope of the present study.We found that the lowest energy surface complexes are completely or partially dehydrated at the MnO 2 surface. Therefore, the generic surface reactions for Pb 2+ can be written as…”
mentioning
confidence: 99%
“…Here we present a detailed study of the structural and dynamic properties of [Mg­(NH 3 ) n ] 2+ and [Ca­(NH 3 ) n ] 2+ clusters with n = 2–6, 8, 10, 20, and 27 through Born–Oppenheimer molecular dynamics (BOMD) simulations. We have employed this powerful methodology with great success in the study of the aqueous solvation of Mg 2+ , Ca 2+ , and Pb 2+ cations ,, as well as in the study of the solvation of several types of metallic molecules. We stress that in these cases nanodroplet cluster models (with around 30 solvent molecules) have quite successfully reproduced the solvation structure observed in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%